Quranic Character Values In Elementary Students Pondok Melati: Nilai Karakter Qurani Pada Siswa Sekolah Dasar Pondok Melati - Mariyati Mariyati; Muhamad Sofian Hadi; Mufti Abqary (Academia Open, 2026)
General Background: Character education is positioned as a foundational component in elementary schooling tocultivate moral, social, and spiritual dispositions from an early stage. Specific Background: Within Islamic educational discourse, Ibn Kathir’s tafsir provides comprehensive Qur’anic moral values grounded in scripture, prophetic traditions, and scholarly interpretations that are relevant to character formation in elementary education contexts. Knowledge Gap: Empirical studies that quantitatively examine the relevance of Ibn Kathir’s character values within contemporary public elementary schools remain limited, particularly at the level of measurable student understanding, school-based implementation, and manifested character traits. Aims: This study examines character education through Ibn Kathir’s perspective and analyzes its relevance to elementary students’ character development in Pondok Melati District. Results: Quantitative findings indicate that students’ understanding of Qur’anic character values, the school implementation of character education, and students’ character traits are all categorized as good, with statistical analysis confirming a significant relationship between value understanding and student character formation. Novelty: This study operationalizes Ibn Kathir’s Qur’anic character values into measurable indicators using a correlational survey approach within public elementary schools. Implications: The findings support the integration of Qur’anic character values into elementary education practices through consistent habituation, teacher exemplification, and contextualized school culture aligned with national character education objectives. Highlights • Students demonstrate good comprehension of Qur’anic moral values• School practices reflect consistent character-based habituation• Student character traits align with Qur’anic ethical principles Keywords Character Education; Ibn Kathir Tafsir; Elementary Education; Quranic Values; Pondok Melati District